Universalism v. Relativism: The Human Rights Debate Around Internalization of Global Norm of Anti-FGM in Gorontalo, Indonesia - Putri, Safriska Desna; Sundrijo, Dwi Ardhanariswari (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2023)
Researches show how people and government of Southeast Asia tend to promote the relativism of norms, and with that challenge the mainstream narrative that promote the universalism of norms. This partially explains the multiple failures of the regionalisation of many global norms in the region. Female Genital Mutilation (FGM), a term that defines any procedure that harms female genital organs, is a traditional practice that is condemned by many international institutions. Anti-FGM has become one of the most important global norms on health issues, officially adopted as a terminology by WHO in 1991 and become resolution in 2008. Under this circumstances, it is widely known that the practice of female children circumcision is still very commonly found in Gorontalo region in Indonesia. In Gorontalo, this practice involved not only health and rational consideration, but most importantly also is involved tradition and beliefs that have been passed down from generation to generation. It is hence contained a particular cultural meaning, which somehow has become the people’s shared characteristics which further defines the identity of the women of Gorontalo. This strong tradition is, naturally, goes against global believe which consider this custom as a violation on children's and human rights. This local dynamics thus lead us to the contestation between the idea of